The Impact of Investment Experience, Financial Literacy And Perception of Ease of Use On The Risk Tolerance of Gen Z Investors In Denpasar City - I Gede Fery Surya Tapa; Komang Irvan; I Nyoman Gede Arya Diatmika; Made Mulyadi (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2026)
The significant increase in the number of retail investors in Indonesia, particularly among Generation Z, has reshaped the dynamics of the capital market; however, this escalation is not always accompanied by adequate financial literacy, which may increase vulnerability to risk and poor investment decisions. This study aims to analyze the influence of investment experience, financial literacy, and perceived ease of use of digital investment applications on the risk tolerance of Gen Z investors in Denpasar City. This research adopts a quantitative approach by distributing questionnaires to respondents selected through purposive sampling and analyzing the data using multiple linear regression supported by validity, reliability, and classical assumption tests. The findings reveal that investment experience, financial literacy, and perceived ease of use each significantly and positively influence risk tolerance, while collectively demonstrating a strong explanatory power for variations in investors’ risk tolerance levels. These results imply the importance of strengthening financial education and responsible digital investment practices to enhance the quality of investment decision-making among young investors in the digital era